Anthropological Linguistics Study on the Lexical and Cultural Meanings of Blora Batik Motif Naming - Nuradita, Rizki Dwi; Nurhayati, NFN (Balai Bahasa Kalimantan Tengah, 2024)
This research aims to classify and explain the lexical and cultural meanings behind the naming of distinctive batik motifs from Blora. The study employs a qualitative method with data consisting of lexicons and information related to the names of Blora batik motifs, obtained through interviews with local batik artisans. Data collection was conducted through recording and note-taking techniques, followed by classification based on linguistic form and cultural background to identify naming patterns of the motifs. The analysis utilizes an anthropological linguistic approach to interpret the cultural meanings embedded in these patterns. The results of the study show that of the 14 distinctive Blora batik motifs examined, the naming of these motifs reflects cultural values, history, and harmonious relationships with nature. The lexical meanings of these motifs can be categorized into monomorphemic forms and phrasal forms that depict cultural entities and local wisdom of Blora. Meanwhile, the cultural meanings emphasize the importance of spiritual values, history, and locally inherited wisdom. Thus, Blora's distinctive batik is not merely an art form, but also embodies the cultural identity of the local community.